Interreligious and values education in Europe: map and handbook - Lähnemann, Johannes; Schreiner, Peter (Comenius-Inst., 2008)
Für das "European Interreligious Encounter" in Rovereto/Italien 2008 hat der Vorsitzende der Peace Education Standing Commission (PESC) of Religions for Peace (RfP) Johannes Lähnemann in Kooperation mit Peter Schreiner eine Europäische Landkarte für Interreligiöses Lernen und Werteerziehung erstellt. Das dazu gehörende Buch enthält aktuelle Projekt- und Länderberichte aus 14 verschiedenen Ländern und informiert über das EU-Forschungsprojekt REDCo: Religion in Education. - For the European Interreligious Encounter in Rovereto/Italy 2008, Johannes Lähnemann, chairman of the Peace Education Standing Commission (PESC) of Religions for Peace (RfP) in cooperation with Peter Schreiner of the Comenius Institut Münster has prepared a European Map of Interreligious and Values Education accompanied by a handbook containing project and country reports. It corresponds the general motto of the encounter - "Shared Values for a Changing Europe".